KESANTUNAN BERBAHASA DEWAN JURI RAGAM ACARA “BERAKSI DI RUMAH SAJA” DI INDOSIAR (KAJIAN SOSIOPRAGMATIK) - Muhammad Hasbullah Ridwan; Nurul Khamidah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Speaking in a good and polite way is a rule in communicating so that communication can run smoothly and the purpose of discussion or the purpose of communication can be achieved. Communication between individuals or groups can occur in various places be it in the family environment, workplace and others. In addition, communications can be found on newspapers, tabloids, wrong magazines and television broadcasts. One of the television shows that shows the existence of communication between people is in various events